(untitled) (Annals of Medical Research, 2021)
Aim: In this prospective study, we aimed to compare the patients scheduled for in vitro fertilization (IVF) with poor ovarian reserve to patients with unexplained infertility in the same age group in terms of sexual dysfunction.Material and Methods: In this prospective study, a total of 146 patients admitted to the IVF center of Ondokuz Mayıs University between June 2018 and December 2018 were included in the study. Fourty-eight of these patients had poor ovarian reserve and 98 were scheduled for IVF due to unexplained infertility. In these patients, the female sexual function index (FSFI) scores were calculated for the diagnosis of sexual dysfunction prior to treatment. In addition, ovarian reserve tests such as cyclic follicle stimulating hormone (FSH) and anti mullerian hormone (AMH) at the beginning of the menstrual cycle were recorded.Results: The mean age of the female patients in the study was 30.2+-5 years. The mean FSFI score was 22.36 +-3.31 and 22.44+-3.53 in the group with poor ovarian reserve and with unexplained infertility, respectively. The prevalence of sexual dysfunction (FSFI score 26.55) in the poor ovarian reserve group was 89.6% (n=48) compared to the unexplained infertility group, which was 93.9% (n=98). The analysis of domains revealed no statistically significant difference between the two groups (p=0,356).Conclusion: Sexual dysfunction is frequently observed in patients scheduled for IVF. Our study showed that there was no difference in sexual dysfunction between the two groups. Interestingly, it was revealed that there was a correlation between FSH levels and satisfaction and pain.It was also interesting that the rate of sexual dysfunction was extremely high in both groups.Keywords: Decreased ovarian reserve; sexual dysfunction; unexplained infertility; ovarian reserve.